'A matter of opinion': British attempts to assess the attrition of German manpower, 1915–1917. Issue 3 (16th April 2017) - Halewood, Louis
Abstract: Revisionist historians of the Western Front have demonstrated that Britain had no alternative but to wage a war of attrition to defeat Germany. However, the effort to assess this process has been neglected in the historiography. This article explores British attempts to gauge the success of their strategy of wearing down German manpower. Efforts in London proved unable to supply a convincing answer. Using General Headquarters' dubious estimates from the front, Field Marshal Sir Douglas Haig argued that his strategy was working. Prime Minister David Lloyd George's inability to confound these estimates shaped his decision to permit the Passchendaele offensive.